CHANGES IN SPERMATOGENESIS IN INFERTILE MIDDLE AGE MEN WITH BENIGN PROSTATIC HYPERPLASIA - Grytsuliak, B.V.; Grytsuliak, V.B.; Bielova, N.V.; Hlodan, O.Ya.; Dolynko, N.P.; Ivasiuk, I.Yo. (World of Medicine and Biology, 2021)
It is established that in men aged 40-50 years already occur signs of benign prostatic hyperplasia with an increase in its volume to (51.2±2.0) and weight – up to (48.3±1.6) g. Cytohistological changes in it are manifested by an increase in the area of stromal components with a decrease in the area of the glandular component up to 56.5 % and 43.5 %, respectively. Under these conditions, arterial blood flow velocity is reduced more than twice (7.70 cm/s vs. 16.5 cm/s) and volumetric blood flow is reduced to 0.03 l/min versus 0.06 l/min. Under these conditions, the testicles are likely to have reduced hemodynamic parameters, reduced testicular volume, diameter of convoluted seminiferous tubules, the number of living, morphologically normal and actively motile spermatozoa and testosterone concentrations in the blood.